Open and robot‐assisted radical retropubic prostatectomy in men receiving ongoing low‐dose aspirin medication: revisiting an old paradigm?. (15th July 2014) - Leyh‐Bannurah, Sami‐Ramzi; Hansen, Jens; Isbarn, Hendrik; Steuber, Thomas; Tennstedt, Pierre; Michl, Uwe; Schlomm, Thorsten; Haese, Alexander; Heinzer, Hans; Huland, Hartwig; Graefen, Markus; Budäus, Lars
<x xml:space="preserve">Abstract</x> Objective To assess blood loss, transfusion rates and 90‐day complication rates in patients receiving ongoing 100 mg/day aspirin medication and undergoing open radical prostatectomy (RP) or robot‐assisted RP (RARP). Patients and Methods Between February 2010 and August 2011, 2061 open RPs and 400 RARPs were performed. All patients received low‐molecular‐weight heparin for thrombembolism prophylaxis. Aspirin intake during surgery was recorded in 137 patients (5.5%). Descriptive statistics and multivariable analyses after propensity‐score matching for balancing potential differences in patients with and without aspirin medication were used to assess the risk of blood loss above the median in patients undergoing open RP or RARP. Results The median blood loss in the open RP cohort with and without aspirin medication was 750 and 700 mL, respectively, and in the RARP cohort it was 200 and 150 mL, respectively. Within the same cohorts, transfusions were administered in 21 and 8% and 0 and 1% of patients, respectively. The 90‐day complication rates in patients with ongoing aspirin medication were 5.8, 4.4, 7.3 and 0% for Clavien grades I, II, III and IV complications, respectively. In multivariable analyses and after propensity‐score matching, prostate volume (odds ratio 1.03; 95% CI 1.02–1.04; P < 0.01) but not ongoing aspirin medication achieved independent predictor status for the risk of blood loss above the median. Conclusions Major surgery such as open RP and RARP can be safely performed in patients with ongoing aspirin medication without greater blood loss. Higher 90‐day complication rates were not detected in such patients. Differences in transfusion rates between the groups receiving and not receiving ongoing aspirin medication may be explained by a higher proportion of patients with coronary artery disease in the group receiving ongoing aspirin mediciation. This comorbidity may result in a higher peri‐operative threshold for allogenic blood transfusion.